Correction of the curve of spee using clear aligner therapy: A finite element analysis of three lower anterior intrusion protocols - José Alejandro Guerrero-Vargas; Carina Cristina Montalvany-Antonucci; Sandra Melisa Velez-Muriel; Natália Couto Figueiredo; Soraia Macari (PLoS ONE, 2026)
Background Correction of the curve of Spee (COS) often requires lower anterior intrusion, which remains one of the least accurate tooth movements in clear aligner therapy (CAT). This limited accuracy may be influenced by the anchorage system or the design of the intrusion strategy. This study aimed to evaluate the movement trends and stress distribution in the lower anterior teeth subjected to three different intrusion protocols using finite element analysis (FEA). Methods Three-dimensional models of the mandibular dentition, periodontal ligaments (PDLs), bone, attachments, and clear aligners were constructed using Materialise Mimics and Materialise 3-matic software. The assembly of the anatomical structures was developed using Autodesk Inventor, and FEA was performed using FeBio software. Three protocols with different anterior intrusion designs were evaluated: S1 (simulation 1) — intrusion displacements of 0.25 mm were applied simultaneously to the canines, central, and lateral incisors; S2 (simulation 2) — intrusion displacements of 0.25 mm were applied only to the lateral and central incisors; S3 (simulation 3) — intrusion displacements of 0.25 mm were applied only to the canines. Total displacement, equivalent strain, and the distribution of minimum and maximum principal stresses were analyzed. Results Simultaneous intrusion (S1) produced the most balanced movement with the lowest stress in the target teeth and controlled bone displacement. Intruding only the incisors (S2) increased PDL stress and anchorage extrusion but also caused minor canine intrusion, indicating force propagation through the aligner. Canine-only intrusion (S3) elevated stress in the canines and produced slight incisor intrusion. Posterior teeth functioned effectively as anchorage in all simulations. Conclusion Simultaneous intrusion of canines and incisors is the most biomechanically efficient approach for COS correction with aligners, minimizing stress and unwanted side effects. Isolated intrusion of either group requires careful planning to manage secondary movements and anchorage control.